Respuesta :

(1) 2x + y = 9
(2) 8x – 2y = 6

You can eliminate the x or the y. I am going to eliminate the y

First multiply the first equation 2x + y = 9  by 2.
2x + y = 9
2(2x + y = 9)
4x +2y = 18
Now we have a new equation that we can use and we can eliminate the y from the other equation because +2y - 2y = 0. Lets do that now and solve for  x.

4x +2y = 18
8x – 2y = 6
12x = 24
12x / 12 = 24 / 12
x = 2
So we found the value of x, which is 2. To find y, insert 2 into one of the original equations. I am going to use 2x + y = 9
2x + y = 9
2(2) + y = 9
4 + y = 9
-4 + 4 + y = 9 - 4
y = 9 - 4
y = 5
y = 5.

Our point is at (x, y) = (2,5)
x = 2
y = 5